2007
DOI: 10.1080/03093640601040244
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb amputations

Abstract: The purpose of the study was to evaluate possible differences between genders in amputation incidence, revascularization activity before and survival after amputation. This population-based study was carried out in a well-defined geographical area, where all vascular surgical consultations and reconstructions are performed in one university hospital. All amputations performed in the region during 1990 -1999 were identified from the hospital central registers. According to patient's identity codes, the Cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 21 publications
(37 reference statements)
11
40
2
Order By: Relevance
“…A rate of 9 per 100,000 person-years was reported in a German city population with a mean age 10 years lower than that for our study population (6), and a rate of 12 per 100,000 personyears was reported in a Dutch population (14). However, a Finnish study has reported a higher incidence of 23 per 100,000 person-years (15).…”
Section: Conclusion -T H I Smentioning
confidence: 45%
See 1 more Smart Citation
“…A rate of 9 per 100,000 person-years was reported in a German city population with a mean age 10 years lower than that for our study population (6), and a rate of 12 per 100,000 personyears was reported in a Dutch population (14). However, a Finnish study has reported a higher incidence of 23 per 100,000 person-years (15).…”
Section: Conclusion -T H I Smentioning
confidence: 45%
“…Our study showed a significantly higher risk for amputation in diabetic men aged Ն85 years. A Finnish population study showed that men have a significantly higher risk of vascular amputation than women (15).…”
Section: Conclusion -T H I Smentioning
confidence: 99%
“…A similar higher prevalence of amputation among males has been observed in other studies. 40,41 The unemployed status of male members can have a direct impact on the family's income and living standards, since in India the male is traditionally the primary earning member of the family. 42,43 This might explain the important role of employment status in determining QoL in amputees, as unemployment may be distressing for an individual and potentially affect his mental functioning, as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Dillingham et al conducted a nine-year survey covering 11 states in the USA from 1988 to 1996, and found that the incidence of amputation was 52.4/100,000 population per year, wherein 82% were due to peripheral vascular disorder. 4 The incidence of amputation due to peripheral vascular disorder increased from 38.3 to 46.2 during this nine-year period, traumarelated amputation decreased from 11.4 to 5.9, and amputation due to malignant tumors slightly decreased from 0.6 to 0.4, while congenital deficiency accounted for 0.8% of all amputations without any change.…”
Section: Introductionmentioning
confidence: 99%